Trusted auditing method of virtual machine based on improved expectation decision method - Junfeng TIAN; Yongchao ZHANG (Tongxin xuebao)
Whether the cloud computing environment is credible is the key factor in the promotion and effective use of cloud computing.For this reason,the expected value decision method in risk decision-making was improved.The usage scenarios was redefined,the cost and benefit of audit scheme was digitized,and a virtual machine trusted auditing strategy based on improved expectation decision method was proposed.Several levels of security protection for the user virtual machine was provided,and the optimal audit scheme was selected autonomously according to the security protection level chosen by the user for the virtual machine.The virtual machine introspection (VMI) technology was used to obtain the virtual machine information that needs to be audited.The designed encryption mechanism was used to protect the security of users selected security protection level,so as to ensure the security of user virtual machine selection audit strategy.Finally,the simulation results show that the scheme has good performance and validity.